Effects of increased body weight and short-term weight loss on serum PCSK9 levels – a prospective pilot study - Filippatos, Theodosios D (Arch Med Sci Atheroscler Dis, 2017)
INTRODUCTION: Proprotein convertase subtilisin/kexin type 9 (PCSK9) is associated with low-density lipoprotein (LDL) catabolism, but its serum concentration is not uniformly associated with cardiovascular disease in clinical studies. Obesity is linked with increased cardiovascular risk, but the effect of increased body weight and short-term weight loss on serum PCSK9 levels is not well studied. MATERIAL AND METHODS: The aim of this prospective pilot study was to assess differences in serum PCSK9 levels (determined with a quantitative sandwich enzyme immunoassay) between otherwise healthy drug-naïve obese subjects and healthy individuals with normal body weight. Additionally, PCSK9 levels were determined at baseline and after a 3-month weight-loss program with a low-fat diet in a randomly assigned subgroup of the obese subjects (n = 15). RESULTS: Obese subjects (n = 35) were older (age: 43 ±11 years) and had significantly higher body mass index, total cholesterol, triglycerides, LDL cholesterol (LDL-C), apolipoprotein B and homeostasis model assessment of insulin resistance (HOMA) index levels, as well as significantly lower high-density lipoprotein cholesterol (HDL-C) concentration, compared with normal-weight subjects (n = 20, age: 35 ±6 years). Serum PCSK9 levels were significantly higher in obese subjects compared with normal-weight individuals, even after adjustment for age, LDL-C, triglycerides, HDL-C, apolipoprotein A1, apolipoprotein B, apolipoprotein E, glucose, insulin and HOMA index levels (p = 0.018). Obese subjects experienced significant weight loss (from 109 ±22 to 104 ±23 kg, p < 0.01), but serum PCSK9 levels did not significantly change after the 3-month weight-loss program. CONCLUSIONS: Serum PCSK9 levels are higher in obese subjects than in normal-weight individuals. Short-term weight loss with a low-fat diet does not significantly affect PCSK9 levels.